2007
DOI: 10.1093/schbul/sbm157
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Brain Changes in Early-Onset Psychosis

Abstract: Progressive losses of cortical gray matter volumes and increases in ventricular volumes have been reported in patients with childhood-onset schizophrenia (COS) during adolescence. Longitudinal studies suggest that the rate of cortical loss seen in COS during adolescence plateaus during early adulthood. Patients with first-episode adolescent-onset schizophrenia show less marked progressive changes, although the number of studies in this population is small. Some studies show that, although less exaggerated, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 73 publications
0
56
1
Order By: Relevance
“…64 Studies in children and adolescents with a first psychotic episode show that most volume abnormalities, including thinner frontal cortical thickness or increased intracranial CSF, are common to bipolar and schizophrenia patients, although they seem to be quantitatively larger in those developing schizophrenia vs bipolar type I. 51,67,69,70 In early-onset psychosis, progressive brain volume changes (mainly reduction in frontal GM volume) seem to be more marked in those who develop schizophrenia than in those who develop other diagnoses. 52 However, it is not clear to what extent this larger reduction is a reflection of the different diagnosis or a severity marker.…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…64 Studies in children and adolescents with a first psychotic episode show that most volume abnormalities, including thinner frontal cortical thickness or increased intracranial CSF, are common to bipolar and schizophrenia patients, although they seem to be quantitatively larger in those developing schizophrenia vs bipolar type I. 51,67,69,70 In early-onset psychosis, progressive brain volume changes (mainly reduction in frontal GM volume) seem to be more marked in those who develop schizophrenia than in those who develop other diagnoses. 52 However, it is not clear to what extent this larger reduction is a reflection of the different diagnosis or a severity marker.…”
Section: Neuroimagingmentioning
confidence: 99%
“…[51][52][53][54] Although neuroimaging studies have shown a different pattern in childhood and early adolescence-onset schizophrenia compared with late adolescence-onset and adultonset ("back-to-front" tissue loss with early parietal gray matter [GM] loss followed by frontal and temporal GM loss in childhood-onset vs GM loss mostly in prefrontal and temporal cortices in adult-onset), there is a tendency to resemble the pattern seen in adult-onset as children become young adults. 55,56 Furthermore, neuroimaging studies in childhood-onset schizophrenia (COS) have reported some results consistent with the adult-onset schizophrenia literature, ie, increased lateral ventricular volume, decreased total and regional cortical GM volumes, decreased hippocampal and amygdala volumes, and increased basal ganglia volumes that progressed during adolescence.…”
Section: Brain Abnormalities In Imaging Studiesmentioning
confidence: 99%
“…In piecing together the complex puzzle of brain abnormality in schizophrenia, the majority of studies have focused on chronically ill populations, but more recently, attention has turned to newly diagnosed, minimally, or nevertreated patients with this disorder. 2,3 Strategically, recruiting such individuals helps to reduce confounders such as age of onset, illness duration, and treatment that may dilute the neuropathological findings in schizophrenia. 4,5 In other words, the ideal participant in MRI research would be in his or her first episode of schizophrenia (FES).…”
Section: Introductionmentioning
confidence: 99%
“…4 Longitudinal volumetric studies involving patients with childhood-onset schizophrenia have shown progressive cortical changes that involve the entire cortex within 5 years and then gradually become limited to the frontal and temporal regions in early adulthood. [5][6][7][8][9][10] It remains unclear whether the structural changes observed in childhoodonset, compared with adult-onset, schizophrenia are associated with disruption of a neurodevelopmental process, as has been suggested by some genetic studies. [11][12][13] Alternatively, structural changes could be associated with chronic illness, positive psychotic symptoms, treatment resistance or a combination of these factors.…”
Section: Introductionmentioning
confidence: 99%
“…5 Studies involving adolescents with schizophrenia have found increased fourth ventricle CSF and reduced prefrontal cortex total, grey and white matter volume, but not reduced total brain volume at diagnosis. 14,15 Among adolescents with undifferentiated psychosis, increases in intracranial CSF and reductions in frontal grey matter have been reported; these changes appear to be less severe than in patients with childhood-onset schizophrenia.…”
Section: Introductionmentioning
confidence: 99%